Um porta-grupos para a psicanálise - Kaës, René (Percurso, 2015)
Realização: Ana Claudia Patitucci, Bela M. Sister, Cristina Parada Franch, Danielle Melanie Breyton, Deborah Joan de Cardoso e Silvio Hotimsky. Colaboração: Paulo Jeronymo Pessoa de Carvalho. Tradução: Andrea Carvalho.